THE SYNTHESIS OF Cr2O3-PILLARED MONTMORILLONITE (CrPM) AND ITS USAGE FOR HOST MATERIAL OF p-NITROANILINE - Karna Wijaya; Iqmal Tahir; Ahmad Baikuni (Indonesian Journal of Chemistry, 2002)
The synthesis of Cr2O3-pillared montmorillonite (CrPM) and its usage for host material of p-nitroaniline have been conducted. The Cr2O3-pillared montmorillonite clays was prepared by a direct ion exchange method. First, the polyhydroxychromium as a pillaring spesies was intercalated into the interlayer region of the montmorillonite clays (purified clay in the monocation form), result in a montmorillonite-polyoxychromium intercalation compound. The precursors/pillaring spesies was not stable, hence it must be stabilized by calcination in order to transform the polyoxychromium via dehydration and dehydroxylation processes into Cr2O3. This oxide constituts the so-called pillar that prop the clay layers apart to a relatively large distance. The Cr2O3-pillared clays as a host material was added into ethanol solution saturated with p-nitroaniline, and mixture was stirred for 24 h at room temperature. The Na-montmorillonite, Cr2O3-pillared clay and p-nitroaniline-Cr2O3-pillared clay (pNA-CrPM) were characterized by X-Ray Diffraction (XRD), Gas Sorption Analysis, Infrared Spectroscopy (FTIR) and Activated Neutron Analysis (ANA) methods. The result of research showed that basal spacing (d001) of Cr2O3-pillared montmorillonite (CrPM) was 18,55 Å, meanwhile the basal spacing of the hydrated Na-montmorillonite was 14,43 Å. The specific surface area of the Cr2O3-pillared montmorillonite was 174,308 m2/g, whereas p-nitroaniline-Cr2O3-pillared clay (pNA-CrPM) was 133,331641 m2/g. This fact indicated that p-nitroaniline has been included into the pore of the Cr2O3-pillared clay.